KESELARASAN STRATEGI DENGAN INTENSITAS PERSAINGAN DAN KECANGGIHAN PRAKTIK AKUNTANSI MANAJEMEN DAN PENGARUHNYA TERHADAP KINERJA PERUSAHAAN MANUFAKTUR DI INDONESIA - , Sekar Akrom Faradiza, Prof. Dr. Gudono, MBA. ([Yogyakarta] : Universitas Gadjah Mada, 2012)
In order to improve and maintain its competitive advantage, companies must choose the appropriate strategy. With appropriate strategy the expected performance can achieved by company. But appropriate strategy is not enough, because the important factors that determine the performance is the alignement between strategy and its contextual variables. This study aimed to test whether the performance of manufacturing companies in Indonesia affected by the alignment of strategy, namely level of competition and sophistication of management accounting practices. There are 33 business units of manufacturing company in Indonesia who were respondents to this study. Cluster Analysis is used to assess the level of sophistication of management accounting practices applied by the company. To test the alignement of strategies and their effect on performance, there-way ANOVA test is used in this study. The result indicate that the performane of manufacturing company in Indonesia does not affected by the alignment of strategy and its contextual variables.